Savage Stone Age - Deary, Terry (Horrible Histories, 2016)
All the most horrible facts about the Groovy Greeks ready for readers to uncover, including why girls ran about naked pretending to be bears, who had the world's first flushing toilet and why dedicated doctors tasted their patients' ear wax. Refreshed with a fantastic new design for 2016, these bestselling titles are sure to be a huge hit with yet another generation of Terry Deary fans.